Interconnected traditions: Semitic languages, literatures, and cultures : a Festschrift for Geoffrey Khan : Volume 1, Hebrew and the wider Semitic world - Coghill, Eleanor; Connolly, Magdalen M.; Hornkohl, Aaron D.; Khan, Geoffrey; Outhwaite, Benjamin M.; Vidro, Nadia; Watson, Janet C. E. (Open Book Publishers, 2025)
"Geoffrey Khan's pioneering scholarship has transformed the study of Semitic languages, literatures, and cultures, leaving an indelible mark on fields ranging from Biblical Hebrew and Aramaic dialectology to medieval manuscript traditions and linguistic typology. This Festschrift, celebrating a distinguished career that culminated in his tenure (2012-2025) as Regius Professor of Hebrew in the Faculty of Asian and Middle Eastern Studies at the University of Cambridge, brings together contributions from a vast and representative array of scholars-retired, established, and up and coming-whose work has been influenced by his vast intellectual legacy. Reflecting the interconnected traditions that Khan has illuminated throughout his career, this volume presents cutting-edge research on Hebrew and Aramaic linguistics, historical syntax, manuscript studies, and the transmission of textual traditions across centuries and cultures. Contributors engage with topics central to Khan's scholarship, including the evolution of the Biblical Hebrew verbal system, the intricacies of Masoretic notation, Geniza discoveries, Samaritan and medieval Judaeo-Arabic texts, and computational approaches to linguistic analysis. As Khan retires from his role as Regius Professor, this collection stands as both a tribute and a continuation of his work, honouring his lifelong dedication to understanding and preserving the linguistic and literary heritage of the Semitic world."--Publisher's website